THE RELATIONSHIP OF MARKETING ORIENTATION AND MANAGEMENT CAPABILITIES WITH ENTREPRENEURIAL SUCCESS OF EVENT MANAGEMENT FIRMS IN SABAH, MALAYSIA - Nora Lawrence Sakai, (Malaysian Journal of Business and Economics (MJBE), 2020)
Event management is a thriving and growing business in many countries, including Malaysia. There are many local entrepreneurs providing various services for events relating to the music and entertainment industry. Hence, these firms need to develop competitive advantages to ensure that their entrepreneurial endeavours are successful. Marketing orientation and management capabilities are two major contributors to business performance. Therefore, in this study, the aim is to determine the level of marketing orientation, management capabilities and entrepreneurial success, as well as to determine the relationship among these variables. This descriptive and quantitative study uses 200 respondents selected using snowball sampling method from among owners and managers of event management firms in Sabah. IBM SPSS 23.0 was used to analyse data gathered from a self-administered questionnaire. Findings showed that marketing orientation and management capabilities were perceived highly but entrepreneurial success was perceived moderately. There is also a direct, significant and moderate relationship between marketing orientation and management capabilities with entrepreneurial success. This study led to the implication that event management firms need to have strong marketing orientation and management capabilities so that their success in the entrepreneurial endeavours is achieved.